Healthcare and economic cost burden of emergency medical services treated non-traumatic shock using a population-based cohort in Victoria, Australia - Stephen Bernard; Cathrine Mihalopoulos; David Kaye; David Anderson; Ziad Nehme; Dion Stub; Andrew A Udy; Elizabeth Davida Paratz; Adam J Nelson; Luke Dawson; David Pilcher; Shelley Cox; et al. (BMJ Open, 2024)
Objectives We aimed to assess the healthcare costs and impact on the economy at large arising from emergency medical services (EMS) treated non-traumatic shock.Design We conducted a population-based cohort study, where EMS-treated patients were individually linked to hospital-wide and state-wide administrative datasets. Direct healthcare costs (Australian dollars, AUD) were estimated for each element of care using a casemix funding method. The impact on productivity was assessed using a Markov state-transition model with a 3-year horizon.Setting Patients older than 18 years of age with shock not related to trauma who received care by EMS (1 January 2015–30 June 2019) in Victoria, Australia were included in the analysis.Primary and secondary outcome measures The primary outcome assessed was the total healthcare expenditure. Secondary outcomes included healthcare expenditure stratified by shock aetiology, years of life lived (YLL), productivity-adjusted life-years (PALYs) and productivity losses.Results A total of 21 334 patients (mean age 65.9 (±19.1) years, and 9641 (45.2%) females were treated by EMS with non-traumatic shock with an average healthcare-related cost of $A11 031 per episode of care and total cost of $A280 million. Annual costs remained stable throughout the study period, but average costs per episode of care increased (Ptrend=0.05). Among patients who survived to hospital, the average cost per episode of care was stratified by aetiology with cardiogenic shock costing $A24 382, $A21 254 for septic shock, $A19 915 for hypovolaemic shock and $A28 057 for obstructive shock. Modelling demonstrated that over a 3-year horizon the cohort lost 24 355 YLLs and 5059 PALYs. Lost human capital due to premature mortality led to productivity-related losses of $A374 million. When extrapolated to the entire Australian population, productivity losses approached $A1.5 billion ($A326 million annually).Conclusion The direct healthcare costs and indirect loss of productivity among patients with non-traumatic shock are high. Targeted public health measures that seek to reduce the incidence of shock and improve systems of care are needed to reduce the financial burden of this syndrome.